Low concentration of exogenous ethanol promoted biomass and nutrient accumulation in oilseed rape (Brassica napus L.). (2nd December 2019) - Wu, Zhimin; Yang, Lan; Jiang, Lihong; Zhang, Zhenhua; Song, Haixing; Rong, Xiangmin; Han, Yongliang
ABSTRACT: With hydroponics culture, we monitored the response of the growth and nutrient accumulation of oilseed rape ( Brassica napus L.) to five ethanol concentrations: 0 mLL −1 (control), 0.0125 mLL −1, 0.025 mLL −1, 0.05 mLL −1, and 0.25 mLL −1, respectively. The results showed that a high concentration of exogenous ethanol (0.25 mLL −1 ) significantly inhibited oilseed rape growth by 52.28%. However, the biomass of oilseed rape with a low concentration of exogenous ethanol (0.0125–0.05 mLL −1 ) manipulation was raised by 16.62–44.08%. A similar result was found on the total nitrogen, phosphorus, and potassium of the oilseed rape. Results of micro-element determination showed that iron and zinc accumulation in oilseed rape was unchanged, while manganese and copper accumulation was increased first and then decreased with increasing ethanol concentration. This study provided a possibility for improving plant growth with low concentration ethanol application in oilseed rape planting.